2008
DOI: 10.1359/jbmr.071010
|View full text |Cite
|
Sign up to set email alerts
|

Bone Fragility Contributes to the Risk of Fracture in Children, Even After Moderate and Severe Trauma

Abstract: We prospectively examined whether the relationship between skeletal fragility and fracture risk in children 9.9 ± 0.3 (SD) yr is affected by trauma level. Bone size relative to body size and humeral vBMD showed similar inverse relationships with fracture risk, irrespective of whether fractures followed slight or moderate/severe trauma.Introduction: Fracture risk in childhood is related to underlying skeletal fragility. However, whether this relationship is confined to low-trauma fractures or whether skeletal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 17 publications
4
89
0
Order By: Relevance
“…However, a prior population-based study demonstrated that skeletal fragility contributed to fracture risk in children, regardless of trauma severity. 41 Since time between visits was up to 1-2 years, censoring at the midpoint of this interval may have created some misclassification of time and consequent imprecision in the observed incidence rates. This, along with the fact that fracture events were not adjudicated by radiology reports, likely biased the results to the null.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prior population-based study demonstrated that skeletal fragility contributed to fracture risk in children, regardless of trauma severity. 41 Since time between visits was up to 1-2 years, censoring at the midpoint of this interval may have created some misclassification of time and consequent imprecision in the observed incidence rates. This, along with the fact that fracture events were not adjudicated by radiology reports, likely biased the results to the null.…”
Section: Discussionmentioning
confidence: 99%
“…(2,3) In both young and older subjects, low areal bone mineral density (aBMD) has been associated with increased fracture prevalence, although most evidence has been obtained in women (4,5) or elderly men, (6) and only limited data are available in boys or young men. (7)(8)(9) osteoporosis, with a similar phenotype in their adult sons, providing evidence for a deficient acquisition of PBM in these men. (11,12) These studies suggested a deficient estrogen exposure as a contributing pathophysiologic mechanism.…”
Section: Introductionmentioning
confidence: 88%
“…(2,3) In both young and older subjects, low areal bone mineral density (aBMD) has been associated with increased fracture prevalence, although most evidence has been obtained in women (4,5) or elderly men, (6) and only limited data are available in boys or young men. (7)(8)(9) An important limitation of dual-energy X-ray absorptiometry (DXA) is that it measures projected aBMD and not volumetric BMD (vBMD). In determining PBM and future facture risk, this has important clinical implications because bone strength depends not only on the amount of bone tissue but also on the diameter, shape, and volumetric bone density, as well as the distribution of cortical and trabecular bone.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded individuals with previous wrist fractures on the contralateral limb or bilateral wrist fractures (n=15). We categorized trauma degree as low, moderate, or high energy based on a modified version of Landin's classification adapted from Clark et al [18] (Table 1). Of the 543 eligible participants with recent fracture (cases), 267 declined participation and 105 consented to participate but did not schedule a measurement appointment.…”
Section: Participantsmentioning
confidence: 99%
“…CIHR Author Manuscript CIHR Author Manuscript Table 1 Trauma degree classification (modified from Clark et al [18] and Farr et al [15])…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%